Upaya Meningkatkan Prestasi Belajar Pendidikan Agama Islam melalui Model Eksperimen - Umi Cholifah (Academy of Education Journal, 2019)
This learning improvement action was carried out through Classroom Action Research (CAR) by applying the "Experimental Learning Model" method, in Islamic Religious Education subjects with the subject matter Knowing the Prayer Principles. The implementation of the CAR follows the steps put forward by IGAK Wardhani whose stages include: planning, acting, observing and reflecting or evaluating. Stages - the stages of recycling and forming cycles. PTK is implemented collaboratively between researchers, observers and peers as supervisors. The process of action to improve Islamic Religious Education material by using the method "Experimental Learning Model") the interest and involvement and activeness of students has increased, students are enthusiastic about doing group work, discussing or answering researchers' questions, 2) achievement or completeness learning outcomes increased from 31.25% in the initial cycle became 62.5% in the first cycle and reached 87.5% in the second cycle.